Action Intentions Modulate Allocation of Visual Attention: Electrophysiological Evidence - Wykowska, Agnieszka; Schubö, Anna (Frontiers in Psychology, 2012)
In line with the Theory of Event Coding (Hommel et al., 2001), action planning has been shown to affect perceptual processing—an effect that has been attributed to a so-called intentional weighting mechanism (Hommel, 2010; Wykowska, Schubö, & Hommel, 2009). This paper investigates the electrophysiological correlates of action-related modulations of selection mechanisms in visual perception. A paradigm combining a visual search task for size and luminance targets with a movement task (grasping or pointing) was introduced, and the EEG was recorded while participants were performing the tasks. The results showed that the behavioural congruency effects, i.e., better performance in congruent (relative to incongruent) action-perception trials have been reflected by a modulation of the P1 component as well as the N2pc (an ERP marker of spatial attention). These results support the argumentation that action planning modulates already early perceptual processing and attention mechanisms.